VacZineNations! as Practice-Led Research (Imaginations: Journal of Cross-Cultural Image Studies, 2020)
VacZineNations! is a collaborative artwork led by Rachelle Viader Knowles and Mkrtich Tonoyan, produced by artists, students, and designers in the UK, Canada, China, and Armenia, and exhibited as part of at Galleri KiT in Trondheim, Norway, and UNAIDS in Geneva, Switzerland in 2017. This paper positions the artwork within the context of practice-led research and dialogic approaches to art-making, identifying a set of nine key characteristics for translocal, dialogue-based art.
Keywords: dialogue-based art; practice-led research; artist/academic; translocality; mobility